Effect of bankruptcy risk on value of conglomerate firms in Nigeria - Emeka, Omaliko; A, Mordi Kelvin (International Journal of Economics, Business and Management Studies, 2023)
The study examined the effect of bankruptcy risk on value of conglomerate firms in Nigeria. Ex post facto design was used and data for the study was collected from the Nigerian Exchange Group (NGX Group) Factbook covering from 2017-2021. The design was used since the data is secondary in nature which cannot be manipulated. The study used key proxy variables of leverage (LEV), liquidity (LIQ), profitability (PROF) and firm size (FS) as a measurement for bankruptcy risk while firm value on the other hand, was proxy using net assets per share (NAPS). Four hypotheses were used in the study while regression model was employed in the data analysis. The results of the study indicate that profitability, liquidity, leverage and company size significantly impacted firm value in Nigeria at 1-5% significant level. The study concludes that bankruptcy risk has influenced firms’ value over the years. Hence, the study is crucial as it exposits the influence of bankruptcy risk on firms value in Nigeria. The study’s outcome should be considered as a signal to company managers when considering their liquidity position, leverage, profitability and company size, as it could be an indication for corporate bankruptcy risk.